Analysis of the Sensing Properties of a Highly Stable and Reproducible Ozone Gas Sensor Based on Amorphous In-Ga-Zn-O Thin Film - Wu, Chiu-Hsien (Sensors (Basel), 2018)
In this study, the sensing properties of an amorphous indium gallium zinc oxide (a-IGZO) thin film at ozone concentrations from 500 to 5 ppm were investigated. The a-IGZO thin film showed very good reproducibility and stability over three test cycles. The ozone concentration of 60–70 ppb also showed a good response. The resistance change (ΔR) and sensitivity (S) were linearly dependent on the ozone concentration. The response time (T(90-res)), recovery time (T(90-rec)), and time constant (τ) showed first-order exponential decay with increasing ozone concentration. The resistance–time curve shows that the maximum resistance change rate (dRg/dt) is proportional to the ozone concentration during the adsorption. The results also show that it is better to sense rapidly and stably at a low ozone concentration using a high light intensity. The ozone concentration can be derived from the resistance change, sensitivity, response time, time constant (τ), and first derivative function of resistance. However, the time of the first derivative function of resistance is shorter than other parameters. The results show that a-IGZO thin films and the first-order differentiation method are promising candidates for use as ozone sensors for practical applications.